Production Planning Analysis Using Forecasting and Aggregate Planning Methods - Silvia, Khurin; Juwita, Himmiyatul Amanah Jiwa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The declining trend in demand for cakes has not been accompanied by changes in production quantities, which still refer to production levels from previous periods, resulting in many unsold products. This has led to suboptimal production cost utilization. This study aims to assist performing production planning using the best forecasting method and aggregate planning strategy to optimize production costs. In this quantitative descriptive study, the analyzed forecasting methods include naive, moving average, weighted moving average, exponential smoothing, and least squares. Meanwhile, the analyzed aggregate planning strategies are the level strategy and the chase strategy. The results show that the least squares is the best forecasting method for cake products, with the smallest error values: MAD of 14, MSE of 300, and MAPE of 9.58, forecasting demand for the next period at 99 cakes. Furthermore, the chosen aggregate planning strategy to forecast demand for the upcoming period is the chase strategy, where the production levels are adjusted to meet demand in each period, resulting in total production planning costs of IDR 18, 809,500.00. Additionally, the production planning costs calculated using the level strategy amount to IDR 20,857,000.00.